2018
DOI: 10.18203/2394-6040.ijcmph20182642
|View full text |Cite
|
Sign up to set email alerts
|

Malaria and malnutrition co-existence among under-five children of tribal dense regions of Odisha: a community based study

Abstract: Background: “Malaria and malnutrition are closely related in the months of hunger gap when malnutrition is at its peak often coincides with rainy season when the number of malaria cases shoot up. The disease combines in a vicious circle. Children sick with malaria are more likely to become dangerously malnourished”. Severely malnourished children with malaria infection may have no fever, or be hypothermic. Proactive screening for malaria in severely malnourished children is needed even if the child has no symp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Malaria and malnutrition are co-existent and synergistic 24 . We found that children with severe malaria were significantly underweight ( P =0.001, unadjusted OR:1.2 (1.08-1.36) ( Table II ), but the wasting levels (WHZ) showed no significant difference between the study group and the uncomplicated malaria group ( Tables II and IV ).…”
Section: Discussionmentioning
confidence: 99%
“…Malaria and malnutrition are co-existent and synergistic 24 . We found that children with severe malaria were significantly underweight ( P =0.001, unadjusted OR:1.2 (1.08-1.36) ( Table II ), but the wasting levels (WHZ) showed no significant difference between the study group and the uncomplicated malaria group ( Tables II and IV ).…”
Section: Discussionmentioning
confidence: 99%
“…Malaria and undernutrition are two leading causes of increased morbidity and mortality rate among children less than 5 years. This complex association persists in an interwoven vicious cycle that coexists in sub-Saharan Africa [ 14 ]. The interaction association between undernutrition and reducing asymptomatic malaria endemicity remains inconclusive with inconsistent findings [ 15 19 ].…”
Section: Introductionmentioning
confidence: 99%